THE IMPERIALISM OF EURO-AMERICAN PSYCHOLOGY IN A NONWESTERN CULTURE: AN ATTEMPT TOWARD AN UMMATIC PSYCHOLOGY (American Journal of Islam and Society, 1997)
General psychology includes many areas of investigation: biologicalbases of behavior, sensation and perception, consciousness andattention, motivation and emotion, conditioning, learning, cognition,language, thinking, remembering and forgetting, intelligence, and personality.During the first half of the twentieth century, psychologistsclassified themselves as structuralists, functionalists, behaviorists,gestaltists, psychoanalysts, existentialists, humanists, or cognitivists.Today, such classifications are little used in the West. If one looks at thepublications of the American Psychological Association and the BritishPsychological Society, psychologists classify themselves according totheir fields or specific topic of hterest, such as social psychology,developmental psychology, abnormal psychology, psychotherapy,counseling, occupational psychology, psychometrics, media, women,and so on. Several tools are used in psychology to study behavior,among them surveys, questionnaires, interviews, observations, experiments,and tests.Psychology is defined as the scientific study of human behavior, andits theories and methods are considered scientific and universal.According to this understanding, there are four important terms that need ...